Genome-wide analysis of extended-spectrum beta-lactamase-producing Escherichia coli from seafood in Bangladesh: population structure, resistome, virulome, and global dissemination patterns - Fahim, Naeem Ahammed Ibrahim; Sarwer, Afsan; Firdous, Zannatul; Rana, Md. Liton; Islam, Md. Saiful; Rahman, Saifur; Pondit, Amrita; Hassan, Jayedul; Walsh, Timothy R.; Farzana, Refath; Rahman, Md. Tanvir (Frontiers in Microbiology, 2026)
ObjectivesThis study aimed to identify multilocus sequence type (MLST), serotype, average nucleotide identity (ANI), antimicrobial resistance genes (ARGs), virulence genes (VGs), and mobile genetic elements (MGEs) from whole-genome sequences of 10 Escherichia coli isolated from seafood in Bangladesh and compared them with the global datasets of beta-lactamase-producing E. coli.MethodsTen E. coli isolates (crab = 3, shrimp = 1, tuna = 6) were subjected to whole-genome sequencing using Oxford Nanopore Technologies (Oxford, UK). In-silico bioinformatics analyses were performed using online tools and Linux-based commands. A systematic advanced search in PubMed identified 722 global genomes of beta-lactamase-producing E. coli for comparative analysis. A population structure and global phylogeny were constructed to illustrate the current status of beta-lactamase-producing E. coli from diverse sources (seafood, human, aquatic, wastewater, and environmental) across countries, based on their STs, ARGs, VGs, MGEs, and serotypes.ResultsBioinformatics analysis revealed that most isolates displayed unique sequence types (STs) and core genome sequence types (cgSTs), while three isolates shared both ST1431 and cgST104784, indicating close genetic relatedness supported by ANI analysis. In shrimp and tuna isolates, both O and H antigens were detected, whereas crab isolates carried either O or H antigens. Pangenome analysis identified 56.4% strain-specific genes, 34.2% dispensable genes, and 9.4% core genes, with functions categorized into clusters of orthologous groups (COGs). Several ARGs, including beta-lactamase genes (CTX-M-15, AmpC, blaDHA-1), were detected across isolates, with crabs harboring the highest number. The VGs were more common in tuna isolates. Plasmids were only detected in crabs (Col440I, IncFIA, IncFIB(pHCM2), and ColRNAI) carrying qnrB4, dfrA17, qacE, mph(A), sul1, blaDHA-1 ARGs, but were absent in shrimp and tuna. Population structure analysis showed that ST345 in Bangladesh closely matched wastewater (Czech Republic) and human (USA) isolates. Some STs overlapped with international records, while others appeared novel, suggesting limited global distribution. Globally, wastewater and human isolates from the Czech Republic showed the greatest similarity to our strains.ConclusionThese findings underscore the potential role of seafood in disseminating beta-lactamase-producing E. coli, highlighting the urgent need for integrated surveillance to mitigate antimicrobial resistance risks in humans, animals, and the food chain.